(untitled) - Omrod, Jeanne Elis (Boston, MA., 2006)
In this update of the 2006 edition, Santrock (educational psychology, U. of Texas at Dallas) and a team of consultants emphasize preparing students for state standards tests such as the PRAXIS II Principles of Learning and Teaching test. Covering the standard topics in the field plus recent research findings on the brain and developmental issues, the text includes case studies, best practices, student and teacher perspectives, chapter exercises, self- assessments, and a glossary. Based on student feedback regarding the CD included in previous editions, multimedia support has been relegated to an auxiliary website
Keywords: Educational psychology,Learning, Psychology of,Motivation in education